GCC entrepreneurs’ business expansion: A case study of Manchester City FC - Aiman Aiman; Tastaftiyan Risfandy; Sabrina Najwa Putri Purnomo; Zahraa orchidta Suwardi (Sebelas Maret Business Review, 2025)
This paper examines the business expansion of Gulf Cooperation Council (GCC) entrepreneurs by acquiring European football clubs, focusing on Manchester City as a case study from the 2008/2009 to 2020/2021 seasons. Football, having evolved from a mere sport into a profitable industry, attracts significant investments from stakeholders, including billionaires and global corporations. This research highlights the increasing trend of Middle Eastern investors acquiring renowned football clubs facilitated by substantial financial resources and strategic management. The analysis reveals that Sheik Mansour's acquisition of Manchester City in 2008 catalysed a remarkable transformation in the club's financial performance, leading to substantial revenue growth and competitive success in domestic and European leagues. By employing financial ratio analysis, the paper evaluates the club's performance pre- and post-acquisition, revealing significant improvements in revenue streams, operational profitability, and overall financial stability. The findings underscore the potential benefits and strategic advantages of such investments in the football industry, contributing to the growing body of literature on sports management and financial strategies in contemporary business.